2018
DOI: 10.1002/cbic.201800475
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Macrocycles Derived from Substituted Triazines

Abstract: A triazine ring derivatized with morpholine, an N‐alkyl‐N′‐BOC‐hydrazine (alkyl=isopropyl or benzyl) and the diethylacetal of glycinylpropionaldehyde undergoes spontaneous dimerization in good yields upon acid‐catalyzed deprotection. The resulting 24‐member macrocycles can be characterized by NMR spectroscopy, mass spectrometry, and single crystal X‐ray diffraction. In the solid state, both homodimers adopt a taco‐like conformation. Although each shows π–π stacking between the triazine rings, different pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…However, even before the adoption of the current method, the yields for cyclization were high. In the initial report, macrocycles were subjected to purification by centrifugation and chromatography [ 20 ]. Yields averaged 90%.…”
Section: Resultsmentioning
confidence: 99%
“…However, even before the adoption of the current method, the yields for cyclization were high. In the initial report, macrocycles were subjected to purification by centrifugation and chromatography [ 20 ]. Yields averaged 90%.…”
Section: Resultsmentioning
confidence: 99%
“…7 Recently, we showed that macrocycles containing 24 atoms could be obtained through the spontaneous dimerization of protected monomers upon treatment with acid. 8 Each monomer presents a BOC-protected hydrazine, a morpholine group, and a tethered acetal. By varying the choice of amino acidusing either glycine or b-alanine-as well as the length of the amino acetal, the tether length is readily manipulated to generate rings of varying sizes.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain crystals suitable for X-ray diffraction, dimethylamine was replaced with morpholine (leading to a shift in nomenclature from G-G to G′-G′ , etc.) because these derivatives are more amenable to crystallization and behave like the dimethylamine analogues in solution. That is, all adopt an ( E )-hydrazone and show identical protonation sites, common NMR features, the same rotamer states, and folded structures.…”
Section: Results and Discussionmentioning
confidence: 99%
“…29 Initial efforts produced macrocycles ranging from 22 to 28 atoms�each a different Murcko framework�displaying different molecular shapes ranging from ones that were compact and folded to those that were extended and flat. 27,28 During the course of these studies, however, two isomeric 24atom macrocycles were prepared�one with glycine and a three carbon acetal (−NHCH 2 CONHCH 2 CH 2 C�N−) and the other with β-alanine and a two-carbon acetal (−NHCH 2 CH 2 CONHCH 2 C�N−). 27 Both showed markedly similar, folded structures in the solid state.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation